Tribological behavior of ceramic disks for application in mixer taps under different lubrication conditions - Ziegler, Marlene; Rothammer, Benedict; Marian, Max; Henzler, Stephan; Beau, Patrick; Bartz, Marcel; Wartzack, Sandro (5th YOUNG TRIBOLOGICAL RESEARCHER SYMPOSIUM, 2022)
There are many tribological systems where technical ceramics are used because of their hardness and high wear resistance. Even in a mixer tap two ceramic disks are integrated in the cartridge. A common problem is the change of the haptic properties during usage, because of changes in the tribological system. Within this work the possibility of reproducing effects relvant for application in model tests is studied. Therefore, a ball-disk-tribometer in oscillating sliding mode was used to test ceramic-ceramic-pairings with varying lubricants. The tests ran without lubricant and with three lubricants of different qualities. Through the addition of any of the lubricants a reduction of the coefficient of friction in comparison to the test runs without lubricant was monitored. To consult the influence of higher temperature due to hot water inflow, all tests were performed at room temperature and at 65 °C. This variation of parameter had no big influence on the test results of tests without lubricant. In the tests with lubricants the coefficient of friction showed a clear dependency on change of temperature. To make a statement with respect to the original system, three mixer taps with different haptically characteristics were used as references